Diagnostic criteria to differentiate pathological procrastinators from common delayers: a re-analysis - Rist, Fred; Engberding, Margarita; Hoecker, Anna; Wolf-Lettmann, Johanne; Fischbach, Eva-Maria (Frontiers in Psychology, 2023)
Detection and treatment of clinically relevant forms of procrastination would be greatly facilitated by diagnostic criteria as formulated for psychological disorders in the Diagnostic and Statistical Manual of the American Psychiatric Association (DSM-5; 2013). A random sample (N = 990) of German university students answered the Aitken Procrastination Inventory (API; Aitken, 1982) and 13 items derived from attempts in the literature to define procrastination. In an earlier analysis eight diagnostic criteria had been derived from these 13 questions which detected 13% of serious procrastination in the sample. In this re-analysis, a subset of only six items strongly related to the first PCA component of the API “central trait procrastination” was selected by Best Subset Regression. An improved Latent Class Analysis strategy for these six items sorted the students again into six well differentiated clusters: A pathological procrastinators cluster (10%) was separated from the clusters of less impaired habitual, average, and occasional delayers. In addition, a cluster of unconcerned procrastinators with strong procrastination but little personal disadvantages and a very small cluster of fast performers emerged. From this cluster solution a rule for a clinical diagnosis of pathological procrastinators was derived. Based on the data the answer steps of the six questions were collapsed into two steps (procrastination feature present or absent). For a diagnosis, two fixed plus at least two out of the remaining five binary criteria must be fulfilled. This diagnostic rule captured 92% of the pathological procrastinators, also 10% of habitual delayers, but no one from the remaining clusters. Despite the loss of differentiation accompanying the transition from ordinal items to binary criteria, these still achieve a satisfying precision. In particular, they separate pathological procrastinators clearly from unconcerned procrastinators. These diagnostic criteria for clinical diagnosis and intervention decisions greatly facilitate the comparison and integration of the results from diverse studies on procrastination.